Correlation and path coefficients in diallel of linseed (Linum usitatissimum L.) - Kumar, Sanjiv; Kerkhi, S.A.; Singh, S.D.; Tripathi, Kirti Mani; Singh, Manender (Annals of Agricultural Research, 2016)
The present study was conducted with 55 genotypes of linseed (Linum usitatissimum L.). The study showed that highly significant and positive association of seed yield per plant was recorded with number of capsules per plant, number of seeds per capsule 1000 grain weight and biological yield per plant. Oil content exhibited significant correlation with biological yield per plant, grain yield per plant and harvest index. Path coefficient analysis for seed yield involving 17 independent variables revealed that number of capsules per plant displayed high order of direct effect on grain yield per plant followed by biological yield per plant, harvest index, secondary branches per plant, 1000 grain weight, linolenic acid content and stearic acid content.